Reciclagem de membranas de osmose inversa por oxidação química e possíveis aplicações - Seibel, Fábio Ivan (2020)
The demand for drinking water has increased due to population growth and the needs for human activities to support this population. To meet this demand, an increasing number of reverse osmosis desalination plants are being installed and operated. However, reverse osmosis membranes tend to reach the end of the life cycle in around two to five years, when they become a solid waste, requiring proper disposal, generating additional costs. Therefore, extending the life cycle of reverse osmosis membranes is a necessity from an environmental and economic point of view. Studies indicate that the recovery of reverse osmosis membranes for the same function is not yet feasible, but, on the other hand, it is possible to transform them into less selective membranes, being an approach to enhance this solid waste. Previous studies indicate the possibility of transforming reverse osmosis membranes into nanofiltration and / or ultrafiltration membranes using oxidizing agents that partially remove the selective layer of the membrane. Most of the published works lack a study of possible applications. This work aimed to transform reverse osmosis membranes through the oxidation of the selective layer with sodium hypochlorite into less selective membranes, and to search for possible applications for recycled membranes. The results show that membranes oxidized at 10,000 ppm.h had a significant increase in permeability but decreased the rejection of electrical conductivity and acetaminophen. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) demonstrates the impact of chlorine attack on the membrane surface, and analysis by Fourier Transform Reflectance Spectroscopy (FTIR) suggests that chlorine oxidation replaced the hydrogen in the amide nitrogen, but the polyamide layer was not fully degraded. Application tests suggest that the recycled membrane can be used for the treatment of brackish and surface water. The recycling of reverse osmosis membranes can be an alternative to give them a second useful life, inserting them in a greater cycle of economic valuation. Keywords: reverse